Anti-Oedipus and Marxist feminism: towards a discussion - Martín, Facundo Nahuel (Estudios de Filosofía, 2021)
This article studies unexplored affinities between the theory of capitalism in Anti-Oedipus and some debates on social reproduction in Feminist Marxism. On the one hand, capitalism, with its movement towards the decoding of flows, tends to dissolve the family under deterritorialized movements. On the other, it presupposes an oedipal (and familiaristic) reterritorialization, for it separates kinship from relations of production, founding a historically specific split. The distinction between axiomatic and capitalist re-territorialization, in this context, appears as an adequate conceptual way to analyze the relation between family and capitalism in feminist-Marxist terms.